RANCANG BANGUN SISTEM KONTROL PADA MESIN CNC ROUTER 3 AXIS - Sutarna, Bhisma Ajuni; Ramdani, Rizki (Jurnal Mahasiswa Terapan, 2025)
The CNC (Computer Numerical Control) router machine is a combination of CNC technology and a router machine, the CNC function is to control the movement of the cutting process and the movement of the spindle motor which functions as a cutting tool player, this machine utilizes a cutting edge rotating on its axis to do milling work (Milling), engrave (engraving) and cutting (cutting). This study aims to create a control system for a 3 Axis CNC Router machine. The method used starts from literature study, identification of needs, installation process, calibration and testing of tools using three axis X, Y, and Z movement modes. The results obtained show that the 3 Axis CNC Router machine uses Arduino UNO components, CNC Shield Expansion Board, A4988 stepper motor driver, GRBL Firmware and GRBL Controller application., can work properly, the precision of each X, Y, and Z axis corresponds to the desired tolerance value of 0.01 mm each and the contours of the engraving on the workpiece do not show deviation.